Peran Sustainability Accounting dalam Meningkatkan Transparansi dan Kinerja Keberlanjutan Perusahaan - Veronica Tania Manirili; Giska Audia Fatima Ina; Janete Firdaus Adele Djawa; Yohanes Pemandi Lian (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Growing pressure from stakeholders and global sustainability challenges has increased the demand for transparent and reliable non-financial disclosures. Although sustainability accounting frameworks such as GRI and ISSB have expanded rapidly, many companies still face inconsistencies in the quality and use of sustainability information. This study aims to explain how sustainability accounting can enhance corporate transparency and sustainability performance, while addressing the gap in previous literature that often discusses these components separately. Using a qualitative library research method, this study analyzes books, journal articles, and official sustainability reporting standards published within the last decade. Content analysis was applied to identify recurring themes related to the role, relevance, and impact of sustainability accounting in organizational practices. The findings show that sustainability accounting strengthens transparency by providing structured and comparable ESG disclosures, enabling stakeholders to assess environmental and social impacts more accurately. The study also finds that sustainability accounting contributes to improved sustainability performance by helping companies evaluate resource efficiency, emissions control, employee welfare, and governance quality. These insights demonstrate that sustainability accounting functions not only as a reporting tool but also as a strategic managerial instrument that supports long-term value creation. The study highlights the urgent need for companies to adopt consistent sustainability reporting frameworks to ensure accountability and maintain legitimacy in an increasingly sustainability-oriented business environment.